The character of the mind : an introduction to the philosophy of mind - McGinn, Colin (Oxford University Press, 1999)
The Character of Mind provides a sweeping and accessible general introduction to the philosophy of mind. Colin McGinn covers all of the main topics--the mind-body problem, the nature of acquaintance, the relation between thought and language, agency, and the self.In particular, McGinn addresses the issue of consciousness, and the difficulty of combining the two very different perspectives on the mind that arise from introspection and from the observation of other people. This second edition has been updated with three new cutting-edge chapters on consciousness, content, and cognitive science to make it the reader of choice on this vital topic.
Keywords: Psychology; psychologie; sociologie; psychologie, klinická psychologie